Wave Model for the Design of Sustainable Coastal Infrastructures at an Industrial Site in Tuban, East Java. (September 2020) - Hendriyono, W; Wibowo, M; Subarkah, A; Aziz, H
Abstract: This study focuses on the use of computational model in the design of a breakwater structure, which aims to determine the propagation pattern of the long-term ocean waves, in order to understand their propagation from the deep waters, and to determine the distribution of their energy around a proposed breakwater construction site. The method used is computational simulation of the wave model using the 2D Boussinesq Wave (BW) Module of MIKE21 software. The simulation used an incoming wave of 4.6 m high, which corresponds to the 100 years return-period value. The results show that the existing breakwater layout can protect the harbour by reducing the incoming waveheight by up to 75%. At the proposed design condition, the propagation pattern of the incoming wave slightly differs from the existing condition. The presence of the slopes on both sides of the channel changes the wave direction outwards due to shoaling effects, and consequently, larger concentration of wave energy occurs at some parts of the proposed breakwater design. Results from the model are useful for the design of the new breakwater structures, which is designed according to the predicted wave energy distribution.